2017
DOI: 10.1039/c6ra27723c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation concerning the effect of mass transfer direction on mean drop size and holdup in a horizontal pulsed plate extraction column

Abstract: A schematic diagram of the horizontal pulsed plate column has been used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Figure a also shows that the higher mass transfer efficiency for butyl than toluene at the same pulsation intensity. The interfacial tension of the butyl is lower than for the toluene, and therefore, at the same pulsation intensity, the butyl has a smaller drop size, higher holdup, and, consequently, higher interfacial area for mass transfer . Therefore, the efficiency of the mass transfer is higher for butyl than for toluene at the same condition; for instance, it is 94.2 versus 82.7 % at a pulsation intensity of 1.4 cm/s.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure a also shows that the higher mass transfer efficiency for butyl than toluene at the same pulsation intensity. The interfacial tension of the butyl is lower than for the toluene, and therefore, at the same pulsation intensity, the butyl has a smaller drop size, higher holdup, and, consequently, higher interfacial area for mass transfer . Therefore, the efficiency of the mass transfer is higher for butyl than for toluene at the same condition; for instance, it is 94.2 versus 82.7 % at a pulsation intensity of 1.4 cm/s.…”
Section: Resultsmentioning
confidence: 95%
“…Figure also illustrates that the overall mass transfer coefficients for butyl are greater than those for toluene in the same condition. The drop size and holdup that are produced from a system with lower interfacial tension are respectively smaller and more numerous than those from a system with high interfacial tension . Hence, the interfacial area that is available for mass transfer and is formed by butyl is greater than that which is formed by toluene; therefore, the overall mass transfer coefficient is larger at the same condition.…”
Section: Resultsmentioning
confidence: 98%
“…By comparing the values of the mean drop size in different operating conditions reported in these studies with the experimental data of this work, one can observe that in the horizontal section, we observe slightly larger droplets compared to the horizontal columns and in the vertical section the opposite manner can be observed and slightly smaller droplets are formed in this section in almost identical conditions. For better demonstration between the values of mean drop size in different columns, Figure 10 exhibits the mean drop size in the current study and those obtained from the correlations proposed by Kagan et al, [54] Miyauchi and Oya, [32] Khajenoori et al, [3] Kleczek et al, [55] and Panahinia et al, [56] versus pulsation intensity at dispersed and continuous phase flow rates of 1.11 Â 10 À6 and 1.25 Â 10 À6 m 3 /s. It can be observed that exerting pulsation into an L-shaped pulsed plate extraction column can form larger droplets compared to traditional horizontal columns.…”
Section: Comparison Of Different Extraction Columnsmentioning
confidence: 99%
“…[37] This situation can usually occur during the startup and shutdown of the column. The experimental and calculated drop diameters showed the highest deviation in the lower end of the mixer-settler regime, [54] Miyauchi and Oya [32] Khajenoori et al [3] Kleczek et al [55] Panahinia et al [56] Column dimension D [54] Miyauchi and Oya [32] Khajenoori et al [3] Kleczek et al [55] Panahinia et al [56] Continuous phase (c) reaching more than 40 %; however, in the dispersion regime, this deviation was less than 8 %.…”
Section: Prediction Of the Mean Drop Sizementioning
confidence: 99%
See 1 more Smart Citation